HE INFLUENCE OF MARKETING COMMUNICATION MIX TOWARD PURCHASE DECISION IN AUTOMOTIVE INDUSTRY (CASE STUDY OF YAMAHA MIO SERIES IN KEDIRI, INDONESIA) - Mohamad Risal Zawawi; Misbahuddin Azzuhri (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research identifies the influence of marketing communication mix on consumer purchase decision to buy Yamaha Mio series in Kediri Regency. In marketing communication mix, there are five variables  namely  advertising, sales promotion, personal selling, public relation, and direct marketing.  By employing appropriate method, this study aims at observing consumer consideration  on consumer purchase decision to buy Yamaha Mio series in Kediri regency. This research used explanatory approach as research method. The data in this research was  obtained from  interview, observation, and questionnaire. Sampling technique used  in this research  is  non-probability sampling  by employing 105 respondents. Likert measurement scale was employed to measure consumer’s answer. The  results show that marketing communication mix partially and simultaneously have  significant  influence on consumer purchase decision to buy Yamaha Mio series in Kediri regency. Based on multiple linear  regressions, it is known  that advertising variable has dominant influence on consumer purchase decision to buy Yamaha Mio series in Kediri regency with the amount of regression coefficient  0.365.  In conclusion,  company must add promotion media to increase consumer attention to use Yamaha Mio series and Yamaha should prepare their promotion activity well before carried out in order to appropriate to the target market. Yamaha also should add more budget on advertising because based on this study has dominant effect to consumer purchase decision.Keyword: Marketing Communication Mix, Consumer Purchase Decision, Yamaha Mio series